HPB P65 Resection margin status and five-year survival following pancreatoduodenectomy for pancreatic ductal adenocarcinoma. (7th December 2022) - Russell, Thomas; Labib, Peter; Aroori, Somaiah
Abstract: Background: Fit patients with a resectable cancer affecting the pancreatic head may be offered pancreatoduodenectomy (PD). Although this remains the only curative intent treatment option, few patients achieve long-term survival as early disease recurrence is common. This study aimed to investigate the correlation between resection margin status and five-year survival in PD patients whose postoperative histology confirmed pancreatic ductal adenocarcinoma (PDAC). Methods: Data was extracted from the Recurrence After Whipple's (RAW) study, a multicentre retrospective cohort study of outcomes following PD performed for pancreatic head malignancy (29 centres in 8 countries, n=1, 484). Patients with postoperative histology suggestive of PDAC were identified and compared to one another by their resection margin status. Five-year survival rates were compared using Fisher's exact test. Results: A total of 885 patients had PDAC (59.6%) and 798 of these (90.2%) had resection margin data available. Of these, 393 (49.2%) had no positive margins (R0), 403 (50.5%) had at least one positive resection margin (R1), and 27 (3.4%) had an incomplete resection where tumour was knowingly left in situ at the time of surgery (R2). Five-year survival was 30.0%, 16.9% and 14.8% in those with R0, R1 and R2 disease, respectively. Patients with R0 disease had significantly higher five-year survival compared to those with R1-2 disease (30.0% vs 16.7%, p<0.00001). Conclusions: In our multicentre international study of PD patients, almost half of all those with PDAC had no positive resection margins. Whilst these patients had improved outcomes compared to those with at least one positive margin, less than a third achieved five-year survival.